The Past, Present, and Future in the Diagnosis of a Neglected Sexually Transmitted Infection: Trichomoniasis - Alexandra Ibáñez-Escribano; Juan José Nogal-Ruiz (Pathogens, 2024)
More than one million curable sexually transmitted infections occur every day. Trichomonas vaginalis is one of the main infections responsible for these epidemiological data; however, the diagnosis of this protozoan is still mainly based on microscopic and culture identification. The commercialization of immunological tests and the development of molecular techniques have improved the sensitivity of classical methods. Nevertheless, the fact that trichomoniasis is a neglected parasitic infection hinders the development of novel techniques and their implementation in routine diagnosis. This review article shows the different methods developed to identify T. vaginalis in population and the difficulties in diagnosing male and asymptomatic patients. The importance of including this parasite in routine gynecological screening, especially in pregnant women, and the importance of considering T. vaginalis as an indicator of high-risk sexual behavior are also discussed.